Multi‐Source Retrospective Analysis Exploring the “Pipeline” Relationship Between Pharmacist Board Certifications, Number of Pharm.D. Graduates, and Pharmacy Residency Candidates Matched - Richard Silvia; Elizabeth LaNou; John Schroader; Brian Lawson (JACCP: JOURNAL OF THE AMERICAN COLLEGE OF CLINICAL PHARMACY, 2026)
ABSTRACT Background Board of Pharmacy Specialties board certification has become a common method of distinguishing pharmacists with advanced expertise in various areas of practice. These certifications are an important achievement for the pharmacy workforce, yet the number of new certifications has declined in recent years. Determining if various factors within the education and training pipeline of pharmacists, such as the number of Doctor of Pharmacy (Pharm.D.) graduates and the number of pharmacy residency candidate matches, are involved in this decline has not been previously studied. Methods This study was a retrospective database review correlating numbers of Pharm.D. graduates and Postgraduate Year (PGY) 1 and PGY2 residency candidate matches to new board certifications annually. Data from each database was aligned to Pharm.D. year of graduation from 2015–2023 for analysis. Correlation analysis was performed for both Pharm.D. graduates and residency candidate matches with new board certifications, as well as multivariate analysis of both factors with new board certifications. Pharm.D. graduate and PGY2 residency candidate matches were also analyzed for correlations (individually) and multivariate effects (together) with their respective aligned specialty certifications. Results The number of Pharm.D. graduates declined over the study time period and showed strong correlations between all new board certifications ( r = 0.95, p < 0.001) and new Board‐Certified Pharmacotherapy Specialist certifications ( r = 0.94, p < 0.001). No significant correlations were found for residency candidate matches (PGY1 or PGY2) and new certifications. Correlation analysis between Pharm.D. graduates and PGY2 residency candidate matches with their aligned specialty certifications showed minimal, if any, significant results. Conclusion Number of Pharm.D. graduates, but not residency candidate matches, showed significant correlations with new board certifications annually. Reasons for these correlations should be investigated further to determine how Pharm.D. graduate numbers affect certification patterns, and how this can be utilized to increase board certifications in the future.